Pengembangan Budidaya Kacang Tanah (Arachis Hypogeae L) Dan Pendapatan Petani Di Desa Manurung Kecamatan Kusan Hilir Kabupaten Tanah Bumbu Provinsi Kalimantan Selatan - Bahrun Bahrun (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2015)
To the effect of observational which is knows technically and economically hit cost, acceptance and peanut farming income at Silvan Manurung. Peanut production average as big as 112.265,02 kg / farmers or as big as 2.263,27 / farmers (2,66 tons / ha) . Farmer acceptance average as big as Rp. 27. 159. 200,00 / farmer or Rp. 31. 952. 000,00 / ha, meanwhile income of groundnut farming average as big as Rp.. 21. 301. 770,83 / farmers or as big as Rp. 25. 060. 906,86 / ha